Case Report: From septic shock to recovery – a battle against lethal necrotizing soft tissue infection - Xue, Yimin; Wang, Na; Wu, Chaoyu; Yang, Hongmei; Zou, Xiongfei; He, Huaiwu; Shi, Yan (Frontiers in Immunology, 2025)
Necrotizing soft tissue infections (NSTIs) are life-threatening surgical emergencies associated with high morbidity and mortality. We report the case of a 40-year-old woman who presented with progressive left lower limb pain and swelling. CT revealed inflammatory changes involving the deep soft tissues. Despite initial surgical debridement, irrigation, and negative pressure wound therapy (NPWT), the patient rapidly deteriorated and progressed to septic shock, requiring intensive care unit (ICU) admission, broad-spectrum antibiotics, advanced life-sustaining support with veno-arterial extracorporeal membrane oxygenation (V-A ECMO), and continuous renal replacement therapy (CRRT). Cultures from the wound drainage identified Streptococcus pyogenes (S. pyogenes), leading to targeted antimicrobial therapy. Ongoing clinical deterioration and elevated myoglobin levels prompted repeated surgical debridements for progressive muscle and skin necrosis. Following multiple staged debridements and multidisciplinary management, the patient achieved hemodynamic stability, successful wound closure, and skin grafting. This case highlights the critical need for timely diagnosis, aggressive surgical and medical management, and coordinated multidisciplinary care in improving outcomes for patients with severe NSTIs.